The Serbian Constitution as a Constitution of aTotal Pluralistic Party State - Aleksandar Molnar (University of Belgrade, 2016)
In the first section of the paper Carl Schmitt’s concept of a total pluralistic state (totale pluralistische Parteistaat) is reconstructed from various writings of his published in the 1930s. The three principal pillars of a total pluralistic party state are considered: constitutional ethics (based on political myth), party pluralism and the totalitarian aspirations of political parties towards their members and clients in the sphere of civil society. In the second section of the paper all three pillars are identified in the Serbian Constitution of 8 November 2006.